THE EFFECT OF INTANGIBLE ASSET INVESTMENT TOWARD FIRM VALUE (An Empirical Study on Manufacturing Companies listed in Indonesia Stock Exchange (IDX) 2012-2016) - Tirzana, Tiara Gita Tirzana B1024141011 (Jurnal Manajemen Update, 2018)
AbstractThis research aims to determine and ascertain the effect of intangible asset toward firm value with profitability, leverage, and firm size as the control variables in manufacturing sector listed in Indonesia Stock Exchange 2012-2016. The independent variable X1 is intangible asset then the control variables are profitability (proxy ROA), leverage (proxy DER), and firm size.Â  The dependent variable is firm value with Tobinâ€™s Q as the indicator. The data used in this research is secondary data derived from annual reports of manufacturing companies. The sample is from purposive sampling, means the sample chosen by the criteria. The criteria chosen 32 companies in 5 years. This study using E-Views version 9.5 as the software to test the regression. This research using random effect model to test the hypothesis. The results of this study indicate that there is positive significant relationship of intangible asset toward firm value. The result of control variable for profitability and leverage are positive significant toward firm value. Meanwhile, the result of firm size indicates negative significant relationship on firm value as control variable.Â Keywords: Intangible Asset, Profitability (ROA), Leverage (DER), Firm Size, Firm Value (Tobinâ€™s Q).ReferencesAdenubga, et al., (2016). Financial Leverage and Firmsâ€™ Value: A Study of Selected Firms in Nigeria. European Journal of Research and Reflection in Management Sciences Vol. 4 No. 1, 2016. ISSN 2056-5992Al Matarneh. 2014. An Empirical Test of the Effect of Intangible Capital on Financial Performance and Market Value in the Jordanian Companies. Global Journal of Management and Business Research: D Accounting and Auditing Volume 14 Issue 2 Version 1.0 Year 2014 Reviewed International Research Journal. Publisher: Global Journals Inc. (USA). Online ISSN: 2249-4588 & Print ISSN: 0975-5853.Behname, et al. 2012. The Relationship between Intangible Assets and the Market Value; Metals Industry of Tehran Stock Exchange Case Study, Australian Journal of Basic and Applied Sciences, 6(12): 115-122, 2012. ISSN 1991-8178Brigham, E.F. and Gapenski, Louis C. 1996. â€œIntermediate finance managementâ€ (5th edition). Harbor Drive: The Dryden Press.Farooq and Masood. 2016. Impact of Financial Leverage on Value of Firms: Evidence from Cement Sector of Pakistan. Research Journal of Finance and Accounting Vol.7, No.9, 2016. ISSN 2222-1697 (Paper) ISSN 2222-2847 (Online).Gamayuni, Rindu Rika. 2015. The Effect of Intangible Asset, Financial Performance and Financial Policies on the Firm Value. International Journal Of Scientific & Technology Research Volume 4, Issue 01, January 2015. ISSN 2277-8616.Kartikasari and Merianti. 2016. The Effect of Leverage and Firm Size to Proftability of Public Manufacturing Companies in Indonesia. International Journal of Economics and Financial Issues. ISSN: 2146-4138.Khumairoh, Kalbuana, dan Mulyati (2016), Pengaruh Leverage, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan, Ahmad Dahlan STIE JakartaLi-Ju Chen and Shun-Yu Chen (2011). The influence of profitability on firm value with capital structure as the mediator and firm size and industry as moderators. Investment Management and Financial Innovations, 8(3))Nazir, Mohammad. 1988. Metode Penelitian [Research Method]. Jakarta: Ghalia IndonesiaNida Nur Fikri, et al, (2017). Pengaruh Intangible Aset, Kinerja Keuangan, Kebijakan Keuangan, terhadap Nilai Perusahaan. ISSN: 2460-6561Norhana Salamudin, Ridzwan Bakar, Muhd Kamil Ibrahim, Faridah Haji Hassan. 2010. Intangible assets valuation in the Malaysian capital market. Journal of Intellectual Capital, Vol. 11 Issue: 3 Available online at https://doi.org/10.1108/14691931011064608Ramadan, Imad Zeyad. 2015. Leverage and the Jordanian Firmsâ€™ Value: Empirical Evidence. International Journal of Economics and Finance; Vol. 7, No. 4; 2015. Published by Canadian Center of Science and Education. SSN 1916-971X. E-ISSN 1916-9728.Robert, et al. 2014. Guide to Intangible Asset Valuation (Revised Version). New York: Linda Prentice Cohen. ISBN: 978-1-93735-225-7Setiadharma S, Machali M (2017) The Effect of Asset Structure and Firm Size on Firm Value with Capital Structure as Intervening Variable. J Bus Fin Aff 6: 298. doi: 10.4172/2167-0234.1000298Shamsuddin, L. (2011), Corporate Financial Management [Manajemen Keuangan Perusahaan]. Jakarta: PT RajaGrafndo Persada.Subramanyam, K. R.and Wild, John J. 2009. Financial Statement Analysis: Tenth Edition. New York: McGraw-Hill. ISBN 978-0-07-337943-2.Weetman, Pauline. 2013. Financial and Management Accounting: An Introduction sixth Edition, p.174. Published by: Pearson.Wolfe, Joseph. (2003). Tobinâ€™s Q as company performance Indicator. Developments in Business Simulation and Experiential Learning, Volume 30, 2003